Heat and Mass Transfer Modeling and Simulation - Hossain, Monwar (IntechOpen, 2011)
This book covers a number of topics in heat and mass transfer processes for a variety of industrial applications. The research papers provide advances in knowledge and design guidelines in terms of theory, mathematical modeling and experimental findings in multiple research areas relevant to many industrial processes and related equipment design. The design of equipment includes air heaters, cooling towers, chemical system vaporization, high temperature polymerization and hydrogen production by steam reforming. Nine chapters of the book will serve as an important reference for scientists and academics working in the research areas mentioned above, especially in the aspects of heat and mass transfer, analytical/numerical solutions and optimization of the processes.